Hung Nguyễn-Viet on managing infectious disease and AMR risk across the livestock revolution - Hung Nguyen-Viet (International Livestock Research Institute, 2021)
Hung Nguyen-Viet of ILRI discussed antimicrobial resistance (AMR) and antimicrobial use in smallholder livestock farming across developing countries, for the plenary session 'Managing emerging infectious disease and AMR risk across the livestock revolution', held at the Prince Mahidol Award Conference PMAC2018. The theme of the conference was 'Making the world safe from the threats of emerging infectious diseases'. The video was recorded in Feb 2018.